DETERMINATION OF TOTAL PHENOL AND FLAVONOID CONTENT OF 96% ETHANOL EXTRACT OF FRESH AND BLACK SUNA ONION BULB (Allium schoenoprasum L.) - Rahmi, Muthia; Dini Amelia, Safitri; Siti Khalida Assyifa, Dayanti; Fitriyanti, Fitriyanti (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Perjuangan Tasikmalaya, 2026)
The use of traditional medicinal plants is increasing because they are easy to find, safer, and affordable. One of the potential local plants from Central Kalimantan is the suna onion (Allium schoenoprasum L.), whose bulbs are used to cook spices and medicine. This study aims to determine the compound, total phenol and flavonoid content in fresh and black suna onion bulbs. Thermal fermentation was carried out for 7 days at ±70°C using an electric slow cooker. Extraction was done using the maceration method and 96% ethanol as a solvent. Qualitative tests for phenol used FeCl₃ and Millon reagents for flavonoids used Shinoda, Bate-Smith, and 10% NaOH reagents. The determination test used a UV-Vis spectrophotometer. For total phenols, gallic acid was used as a comparator, Folin-Ciocalteau as a reagent, with a wavelength of 760 nm. For total flavonoids, quercetin was used as a comparator, and AlCl3 reagents with a wavelength of 415 nm. The qualitative test showed fresh and black suna onion bulbs contained positive phenol and flavonoid compounds. Quantitative results showed an increase in phenolic content from 0.733 ± 0.095 mg Gallic Acid Equivalent(GAE)/g (fresh) to 11.024 ± 0.165 mg GAE/g (fermented) and total flavonoid content from 15.310 ± 0.372 mg QE/g (fresh) to 30.786 ± 0.179 mg QE/g (fermented). Based on these results, it can be concluded that the fermentation process increases the levels of phenolic compounds, flavonoids, and total phenolics in the suna onion bulbs, thus potentially developing them as a traditional medicinal ingredient. This is due to chemical changes that occur during the thermal fermentation process (Maillard reaction).